Simulasi Kejadian Banjir Sungai Way Kandis Ruas Polinela Untuk Beberapa Kala Ulang - Kelik Istanto (Jurnal Ilmiah Teknik Pertanian - TekTan, 2019)
The effort to control waterâ€™s destructive power, in this case is flooding due to overflowing Kandis river, needs to be done to minimize the negative impacts. The main data in flood control infrastructure planning is discharge. The discharge calculation and simulation are required in some return periods. The objectives of research are delineate of catchment area, land cover of catchment area mapping, calculate of maksimum areal rainfall, calculate of flood discharge, and flood simulation of Kandis river in Polinela section base on flood. Kandis river catchment area of the Polinela section was 402.5 hectares and known that type of land cover consists of 15% open land, 20% vegetated land, 50% settlement, and 15% commercial area.The results shown that return period discharge in 2, 5, 10, 20, 25, 50, and 100 year are 9,89 m3/s, 11,81 m3/s, 13,07 m3/s, 14,29 m3/s, 14,68 m3/s, 15,86 m3/s, and 17,04 m3/s. By assuming there will be 1,5 % growth of settlements and commercial areas in catchment area land use as constantly number, 10 years forward, the return period discharge in 2, 5, 10, 20, 25, 50, and 100 year are 10,34 m3/s, 12,33 m3/s, 13,66 m3/s, 14,93 m3/s, 15,33 m3/s, 16,57 m3/s, and 17,80 m3/s. While by assuming there will be 3 % growth of settlements and 1 % growth of commercial areas in catchment area land use as constantly number, 10 years forward, the return period discharge in 2, 5, 10, 20, 25, 50, and 100 year are 10,58 m3/s, 12,63 m3/s, 13,99 m3/s, 15,29 m3/s, 15,70 m3/s, 16,97 m3/s, and 18,23 m3/s.Â Keywords :river, flood, discharge, flood simulation.